Mine technical system with repeated geotechnology within new frames of sustainable development of underground mining of caved deposits of the Zhezkazgan field - Dossanbay Bekbergenov; Gulnar Jangulova; Khaini-Kamal Kassymkanova; Bakytbek Bektur (Geodesy and Cartography, 2020)
The article outlines the principles of design of repeated geotechnology at the development of reserves in the conditions of collapsed deposits of the Zhezkazgan field for the purpose of rational management of underground mining processes. This is an integral design principle of the mine technical system with repeated geotechnology, and the foundation for the practice of designing and operation of the subsoil at the development of mineral deposits. At the designing of a mine technical system with repeated geotechnology aimed at the development of collapsed subsoil reserves, the risks and natural and man-made emergencies related to the production are taken into account. Under modern conditions, mining design cannot be employed in isolation from the principles of sustainable development, which implies not only orthodox meaning but also the development that ensures society existence without threatening the needs of future generations. In this connection, the ongoing research incorporates designing of mine technical systems with due account for the principles of sustainable development, which correspond to the current priority direction related to the development of repeated geotechnology within new frames of sustainable development of repeated underground mining of reserves in the conditions of collapsed deposits of the Zhezkazgan field. This contributes to the efficient use of resource-replenishing repeated geotechnology and the possibility of the most complete development of the georesource subsoil potential due to the enhancement of the ore potential at the operation of underground mines of Kazakhmys Corporation Ltd., which is one of the largest copper mining companies in the world.